A DNA‐Programmed Liposome Fusion Cascade. Issue 43 (23rd August 2017) - Löffler, Philipp M. G.; Ries, Oliver; Rabe, Alexander; Okholm, Anders H.; Thomsen, Rasmus P.; Kjems, Jørgen; Vogel, Stefan
Abstract: Chemically engineered and functionalized nanoscale compartments are used in bottom‐up synthetic biology to construct compartmentalized chemical processes. Progressively more complex designs demand spatial and temporal control over entrapped species. Here, we address this demand with a DNA‐encoded design for the successive fusion of multiple liposome populations. Three individual stages of fusion are induced by orthogonally hybridizing sets of membrane‐anchored oligonucleotides. Each fusion event leads to efficient content mixing and transfer of the recognition unit for the subsequent stage. In contrast to fusion‐protein‐dependent eukaryotic vesicle processing, this artificial fusion cascade exploits the versatile encoding potential of DNA hybridization and is generally applicable to small and giant unilamellar vesicles. This platform could thus enable numerous applications in artificial cellular systems and liposome‐based synthetic pathways. Abstract : Hot fusion : Membrane fusion mediated by the hybridization of lipid‐oligonucleotide conjugates (LiNAs) allows rapid content mixing with low leakage for small liposomes and giant unilamellar vesicles at elevated temperatures of 37 °C and 50 °C. A three‐stage fusion sequence controlled by orthogonal sets of complementary LiNAs was demonstrated at 50 °C.